The role of satisfaction in cultural activities’ word-of-mouth. A case study in the Picasso Museum of Málaga (Spain) - María Jesús Carrasco-Santos; Antonio Padilla-Meléndez (Tourism & Management Studies)
Word-of-mouth has become a relevant area of tourism research over recent decades. However, the effect of tourists’ emotions on these recommendations is an underdeveloped area, particularly in cultural tourism, which, in terms of tourist numbers, is the second most important sector in countries with significant tourism industries, such as Spain. Taking stock of recent advances in cultural tourism, this paper explores specific factors that can affect visitor’s recommendations of a museum, in this case the Picasso Museum in Málaga (Spain). In a novel approach, an experiment (involving a guided tour of some of Picasso’s shortlisted works and painting a self-portrait) was conducted with 127 first-time Picasso Museum visitors (52.8% Spaniards and 47.2 % international visitors). The results show that strengthening the activation of emotions in tourists and non-tourists during cultural activities has a positive effect on their satisfaction, thereby positively influencing their word-of-mouth about the museum.